Terminal value: Building the alternative Bloomberg - Christopher Wood; Alasdair King; Ruth Catlow; Brett Scott (Finance and Society, 2016)
In this essay we propose a reframing of the Bloomberg Terminal, an interface used to track financial trades and values, by using it as a creative, critical and curatorial device to explore the relationship between the art and finance. To contextualise this approach, we offer a history of the Bloomberg Terminal alongside an analysis of the power of interfaces to shape both the user and the represented information. We use the terminal as a way to critique the relationship between art acquisition and financial trading companies. We then describe some outcomes of a series of workshops themed around the idea of "building an alternative Bloomberg". We conclude by offering some potential applications of a re-framed Bloomberg Terminal as an open and modular interface for engaging with issues around art and finance, both in terms of content and curation.
Keywords: 300; Curation; interfaces; art market; open-source; representation; value